Synthesis and Molecular Docking Studies of N’-benzoylsalicylhydrazide derivatives as antituberculosis through InHA enzym inhibition - Harry Santosa; Galih Satrio Putra; Tegar Achsendo Yuniarta; Tutuk Budiati (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2018)
The specific aims of this study is to synthesize and to study the possible mechanism of N’-benzoylsalicylhydrazide derivatives as an antituberculosis agent through InhA (Enoyl acyl carrier protein reductase) inhibition using in silico method. Five analogues of N’-benzoylsalicylhydrazide were synthesized using microwave irradiation from methyl salicylate as starting material, which yielded 80-90% product on average. This indicates a considerable improvement in terms of effectivity and efficiency, compared to the more conventional method using reflux condition. Character-ization of the compounds were subsequently carried out by UV, FTIR, 1H-NMR, 13C-NMR spectroscopy, which confirmed that the compounds had been successfully synthesized. Ultimately, molecular docking was performed using Molegro Virtual Docker (MVD) on the active site of InhA enzyme to predict the activity of the compounds. The results showed that all compounds performed comparatively well against N-(4-Methylbenzoyl)-4-benzylpiperidine as the native ligand and also yielded lower docking score than isoniazide (INH). From this study it can be concluded that N’-benzoylsalicylhydrazide derivatives could be synthesized using microwave irradiation with good product yield and all of the synthesized analogues are suggested to possess antituberculosis activity via InhA enzyme inhibition. In vitro activity will have to be determined in the future to validate whether N’-benzoylsalicylhydrazide derivatives perform well as a potential antituberculosis agent.